Purification of Antihemophilic Factor (Factor VIII) by Amino Acid Precipitation* - Wagner, Robert H; McLester, William D; Smith, Marion; Brinkhous, K. M (Thrombosis and Haemostasis, 1964)
1. The use of several amino acids, glycine, alpha-aminobutyric acid, alanine, beta-alanine, and gamma-aminobutyric acid, as plasma protein precipitants is described.2. A specific procedure is detailed for the preparation of canine antihemophilic factor (AHF, Factor VIII) in which glycine, beta-alanine, and gammaaminobutyric acid serve as the protein precipitants.3. Preliminary results are reported for the precipitation of bovine and human AHF with amino acids.